Mood and Emotion Effect on Auditor Judgment and Decision-Making: A Systematic Literature Review - Septiari, Dovi; Sofyani, Hafiez (International Journal of Economics, Management and Accounting, 2025)
This study analyzes the trends, progress, and opportunities for future research on the relationship between emotions, moods, and auditors’ judgment and decision-making (JDM). We included 24 articles from the Scopus database through a systematic review process using the framework of Hoque (2014) in our literature review. Bibliometric analysis shows interesting developments in the topics of mood, emotion, and auditors' JDM. In particular, the results highlight the evolution of publications in top accounting journals, theoretical development, research context and setting, methods used, and statistical analysis tools. The findings also map the study areas covering five main topics: risk and probability assessment, risk decisions, ethical assessment, conflict resolution, and commitment to professional decisions. In general, previous studies show that emotions and mood can influence auditor judgment when assessing the risk and probability task, affect conservatism, ethical judgment, conflict resolution strategies, and commitment to the profession. One limitation is that the number of articles is small because the related studies are underexplored. Nevertheless, this study contributes to mood and emotion research on auditor JDM by discussing research trends, highlighting current study progress, and identifying future research gaps. We highlight opportunities for further exploration in this field.